Physiological Effects of Dietary Amino Acids on Gut Health and Functions of Swine - Yang, Zhongyue; Liao, Shengfa F. (Frontiers in Veterinary Science, 2019)
Gut health has important implications for animal’s overall health status and nutrient utilization, due to its various functions including digestion and absorption of nutrients, secretion of mucin and immunoglobulins, and selective barrier protection against harmful antigens and pathogens. Both the basic anatomical structure of the gut (such as epithelial cells) and its luminal microbiota play important roles for maintaining gut health and functions. The interactions between epithelial cells and luminal bacteria have significant impact on host nutrition and health through the metabolism of dietary components. Amino acids, which are major nutrients for pigs, are not only obligatory for maintaining intestinal mucosal mass and integrity, but also supporters of the growth of microorganisms in the gut. Dietary amino acids are the major fuel of the small intestinal mucosa. Furthermore, glutamate, glutamine, and aspartate are the major oxidative fuel of the intestine. Emerging evidence shows that arginine activates the mTOR signaling pathway in the small intestine. Utilization of glycine by the small intestinal mucosa to synthesize glutathione is a physiologically important pathway, and the role of glycine as a powerful cytoprotectant has been recognized. The major end products of methionine and cysteine metabolism are glutathione, homocysteine and taurine, which play important roles in the intestinal immune responses. Threonine is highly utilized by the gut and is particularly important for mucin synthesis and maintenance of gut barrier integrity. Moreover, either a deficiency or an excess of dietary threonine can reduce the synthesis of intestinal mucosal proteins and mucins in young pigs. Many new functions of amino acids on gut health and functions have been discovered in recent years. Thus, this review paper provides some up-to-date knowledge for industry application of dietary amino acids to enhance swine gut health and functions, and this paper will also provide a comprehensive reference for further scientific research in this regard.